2004
DOI: 10.1128/aac.48.9.3396-3401.2004
|View full text |Cite
|
Sign up to set email alerts
|

A Mucoadhesive Polymer Extracted from Tamarind Seed Improves the Intraocular Penetration and Efficacy of Rufloxacin in Topical Treatment of Experimental Bacterial Keratitis

Abstract: Bacterial keratitis is a serious infectious ocular disease requiring prompt treatment to prevent frequent and severe visual disabilities. Standard treatment of bacterial keratitis includes topical administration of concentrated antibiotic solutions repeated at frequent intervals in order to reach sufficiently high drug levels in the corneal tissue to inhibit bacterial growth. However, this regimen has been associated with toxicity to the corneal epithelium and requires patient hospitalization. In the present s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 30 publications
1
41
0
1
Order By: Relevance
“…TG is composed of (1→4)-β-D-glucan back-bone substituted with side chains of α-D-xylopyranose and β-D-galactopyranosyl(1→2)-α-D-xylopyranose linked (1→6) to glucose residues [20] . It has been used in the development of various drug delivery systems due to its hydrophilic and bioadhesive properties [21][22][23][24][25][26][27] . Although TG shows presence of non-sterically hindered hydroxyl groups, very few reports mentioned the use of pure TG in chemically crosslinked hydrogels [28] .…”
Section: Research Papermentioning
confidence: 99%
“…TG is composed of (1→4)-β-D-glucan back-bone substituted with side chains of α-D-xylopyranose and β-D-galactopyranosyl(1→2)-α-D-xylopyranose linked (1→6) to glucose residues [20] . It has been used in the development of various drug delivery systems due to its hydrophilic and bioadhesive properties [21][22][23][24][25][26][27] . Although TG shows presence of non-sterically hindered hydroxyl groups, very few reports mentioned the use of pure TG in chemically crosslinked hydrogels [28] .…”
Section: Research Papermentioning
confidence: 99%
“…Tamarind seed polysaccharide was also investigated for ocular delivery of rufloxacin and ofloxacin to treat bacterial keratitis experimentally induced by Pseudomonus aeruginosa and Staphylococcus aureus in rabbits. 105 The result indicated significantly increment in intra-aqueous penetration of drugs in both infected and uninfected rabbit eyes. The use of tamarind seed polysaccharide improved the prolongation of precorneal residence time and drug accumulation by these formulations.…”
Section: Ocular Drug Deliverymentioning
confidence: 84%
“…[103][104][105][106][107] The high viscosity and mucoadhesive property of tamarind seed polysaccharide make it as a suitable excipient in various ocular formulations for increasing the residence time for various drugs on the cornea. A tamarind gum based in situ gelling ocular dosage form of pilocarpine was developed and evaluated for its miotic potential.…”
Section: Ocular Drug Deliverymentioning
confidence: 99%
“…These results suggested that TSP is able to prolong the precorneal residence time of the antibiotic and enhance drug accumulation in the cornea, thereby increasing the intraaqueous antibiotic penetration. (Ghelardi et al, 2004).…”
Section: Eye Dropsmentioning
confidence: 99%